I tempi giusti. Riconfigurazioni del lavoro sociale post Covid-19 - Mascagni, Giulia (SocietàMutamentoPolitica, 2023)
The spread of the new Sars-CoV-2 coronavirus marked the start of a long phase of health emergency and quickly led to the adoption of an articulated strategy to contain the contagion. Starting from March 2020, this had important effects on the main areas of individual and collective life also in our country. Priorities of intervention and unprecedented challenges have therefore been imposed on organizations and institutions first of all in the health sector but no less in the economic and social sphere. The aim of the article is to outline an updated profile of the rhythms and professional strategies of social work in Tuscany. Taking advantage of some key concepts and giving voice to the operators through some recent research results, the article analyzes the paths of reorganization of the times and working methods of those who work with the most fragile and vulnerable and question the adequacy of spaces for individual planning and sustainability, with a dedicated attention to the intertwining of individual time and social time.